Cash Distribution Effectiveness during the Covid-19 Pandemic in Prosperous Village Abadi, Tolangohula District, Gorontalo Regency - Umar Sako Baderan; Dian Fitriani Karim (PSPP JOURNALS, 2022)
This study aims to determine the effectiveness of the distribution of Direct Cash Assistance (BLT) during the Covid-19 pandemic in Makmur Abadi Village, Tolangohula District, Gorontalo Regency. This research uses a qualitative approach with a descriptive type of research. The results of the study based on research findings, it was found that: the distribution of Direct Village Fund Cash Assistance during the Covid-19 pandemic in Makmur Abadi Village, Tolangohula District, Gorontalo Regency did not fully meet 7 indicators if assessed based on 7 indicators of effectiveness. Of the 7 indicators, there are 3 indicators that can be said to be effective, namely indicator 1. Clarity of goals to be achieved, Indicator 6. Availability of facilities and infrastructure, and indicators 7. The educational supervision and control system seen from BLT-DD cannot be divided equally for all residents affected by Covid-19 according to existing regulations. Meanwhile, there are 4 indicators that are not effective, namely indicators 2. Clarity of strategy for achieving goals, indicators 3. A solid policy analysis and formulation process, indicators 4. Careful planning, and indicators 5. Preparation of appropriate programs. Due to the change in poor criteria for recipients, initially there were 14 poor criteria that had to be met by the community, turned into 9 poor criteria according to existing regulations.